Evidance Based Practice Penerapan Terapi Kompres Air Hangat di Leher untuk Mengurangi Nyeri Kepala - Mongi, Thirsa; Mongkol, Klaudya Gabriela (JURNAL ILMIAH KESEHATAN MANADO, 2025)
When someone suffers from hypertension, signs and symptoms will appear, namely pain in one part of the neck. Pain or stiffness in the neck muscles is caused by increased pressure on the walls of blood vessels in the neck area, resulting in obstructed blood flow, and the end result of metabolism in the neck area due to lack of oxygen and nutrients. Pain felt by people with hypertension will interfere with daily activities. Non-pharmacological treatment can reduce pain and can be done individually. The use of warm compresses is more effective for painful areas that can reduce muscle spasms caused by neuronal ischemia that inhibits the transmission of pain stimuli, causing vasodilation and increased blood flow in the area. And applying warm compresses does not have negative impacts. The purpose of this study was to reduce pain by applying warm compresses to the neck area in the elderly Mrs. S. with hypertension in a nursing home. The evaluation results showed that warm compress therapy reduced pain in Mrs. S from a pain scale of 7 down to 4. The conclusion is that there was a decrease in pain in Mrs. S with hypertension experiencing acute pain after being given warm compress therapy to the neck area.